2008
DOI: 10.1590/s0102-36162008000700002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da deformidade estética após a tenotomia da cabeça longa do bíceps na artroscopia do ombro

Abstract: Avaliação da deformidade estética após a tenotomia da cabeça longa do bíceps na artroscopia do ombro Avaliação da deformidade estética após a tenotomia da cabeça longa do bíceps na artroscopia do ombro * Assessment of esthetic deformity after tenotomy of the long head of the biceps in shoulder arthroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Besides the concern with the cosmetic aspect, the possible deficit of strength at the level of the elbow and forearm is a recommendation for tenodesis instead of tenotomy, in patients under 55 years of age (3) . Almeida et al (14) did not find statistical significance when they performed the cross-evaluation between the patients' ages and the esthetic complaint of residual deformity.…”
Section: Discussionmentioning
confidence: 95%
“…Besides the concern with the cosmetic aspect, the possible deficit of strength at the level of the elbow and forearm is a recommendation for tenodesis instead of tenotomy, in patients under 55 years of age (3) . Almeida et al (14) did not find statistical significance when they performed the cross-evaluation between the patients' ages and the esthetic complaint of residual deformity.…”
Section: Discussionmentioning
confidence: 95%
“…Walch et al 8 reported the difficulty in assessing the presence of deformity in obese or elderly patients with poor muscle tone, eventually classifying them as doubtful. Almeida et al, 22 also observed in a statistically significantly manner (p = 0.005) that obese patients perceive less the aesthetic deformity.…”
Section: Discussionmentioning
confidence: 85%
“…Boileau et al 21 reported that their patients perceived the deformity in 66.6% of cases where isolated tenotomy of LHB was performed, without clinical or aesthetic significance. Almeida et al 22 found aesthetic complaint in 35.1% of the sample. Maynou et al 13 noticed complaint to the asymmetry of the UL in only 5% of their patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In another prospective cohort study, Almeida et al 35 evaluated the presence of esthetic deformity after arthroscopic LHB tenotomy and concluded that the Popeye deformity was present in 35.1% of the sample. Male patients, those with BMI below 30, and those who were operated on the dominant limb had more esthetic complaints.…”
Section: Resultsmentioning
confidence: 99%